CORPORATE SOCIAL RESPONSIBILITY (CSR) AND YOUTH EMPOWERMENT IN OHAJI/EGBEMA, IMO STATE (2010–2020) - Ihemadu, Michael C. N.; Osimiri, Eugene Oguwuike (African Journal of Social and Behavioural Sciences, 2025)
This paper examines the corporate social responsibility (CSR) initiatives implemented by oil and gas companies in the Ohaji/Egbema Local Government Area (LGA) of Imo State, Nigeria, with a specific emphasis on their impact on youth empowerment from 2010 to 2020. Utilizing a robust methodology that includes a thorough review of academic literature, governmental reports, documentation from non-governmental organizations (NGOs), and various media sources, the research identifies a diverse array of CSR interventions. These include scholarship programs, vocational training, infrastructure development, microfinance opportunities, and community engagement processes. The study critically evaluates both the scope and sustainability of these initiatives, assessing not just their geographical reach but also their capacity to foster enduring change within the community. It examines several structural barriers that hinder the effectiveness of these CSR efforts in promoting youth employment and entrepreneurship, including project discontinuity, insufficient community involvement, inadequate monitoring and evaluation systems, environmental degradation, and governance complexities. Findings indicate a mixed outcome; while companies have documented a multitude of community projects, significant improvements in youth employment rates and sustainable entrepreneurial outcomes are largely absent. These shortcomings can be attributed to the identified barriers, which have hindered the long-term effectiveness of CSR activities. In conclusion, the paper presents a series of strategic recommendations aimed at enhancing the effectiveness of CSR initiatives. It highlights the necessity of co-designing programs in partnership with the youth to ensure that they are aligned with their needs and aspirations. Furthermore, it advocates for the implementation of comprehensive impact evaluation frameworks to effectively monitor progress and outcomes.